Simulation of the precision limits of plastic scintillation detectors using optimal component selection - Lacroix, Frédéric (American Association of Physicists in Medicine, 2010)
Purpose: The purpose of this work was threefold: First, to determine which type of charge-coupled device (CCD) would provide the best dosimetric precision for plastic scintillation detectors (PSDs); second, to design a high-photon-efficiency PSD system by optimizing its signal-to-noise ratio (SNR) using off-the-shelf technology; and third, to establish the spatial, temporal, and dose precision limits of such a PSD system. The authors have attempted to design a dosimetric tool suitable for radiotherapy treatment modalities employing small fields or fast temporal modulation of the radiation fields, and to explore the current precision limits of PSD systems. Methods: The authors used an SNR simulation model to design and calculate the dosimetric precision of a PSD employing a fiber taper to couple the optical fiber to the photodetector. The authors also used the SNR simulation model to evaluate the impact of the photodetector performance characteristics on the SNR and to establish the spatial, temporal, and dose precision limits. Results: The authors found that a high-photon-efficiency PSD can provide a precision of 1% in 45 μs of integration time for a dose rate of 400 cGy∕min when a single image is taken, detect a dose of 1 cGy with a detector volume of 0.0007 mm(3), and image over 15 000 detectors with a precision of 1% on a 30.7×30.7 mm(2) CCD imaging area. Conclusions: These characteristics establish that PSDs theoretically constitute a suitable dosimetric tool for radiotherapy treatment modalities employing small fields or fast temporal modulation of the radiation fields.